ANALYSIS OF THE OFFER OF FITNESS SERVICE PROVIDERS IN NORTH GREAT PLAIN REGION - Lenténé Puskás, Andrea; Hidvégi, Péter; Pucsok, József Márton; Czeglédi, Hanna Orsolya; Bíró, Melinda (Acta Carolus Robertus, 2021)
With healthy lifestyle getting more widespread, demand for sports services is growing among health-conscious consumers as well. The present study was conducted among fitness service providers (n = 24) in North Plain Region. During our research we sought to find out how these service providers develop their supply elements and are these elements in line with the demand trends? Semi-structured interviews were analyzed by content analysis, which were partially processed using Excel software. Mean and standard deviation were calculated when evaluating the results.The results show that the fitness service providers strive for both extensive and intensive development in their basic and ancillary services, which results in a fairly large number of fitness equipment, air-conditioned rooms suitable for group trainings, parking lots and wellness services that are tailored to consumer fitness trends.
Keywords: Fitness services; class or training types; trends